Interactive E-learning environment for power amplifier in IC - Miao, Weiyang (Nanyang Technological University, 2021)
With the development of technology, many things have a trend of evolving from offline to online. Over the years, the traditional teaching method has also been moving towards the format of interactive e-learning. Especially after experiencing the covid-19 pandemic, more and more schools have tried and started delivering online education, and nowadays the online learning model has become very important. This final year project will take the interactive e-learning mode as the core and use it to explain a very important topic: the power amplifier in IC design. This project will combine hardware and software to allow users to effectively learn the topic of power amplifiers and experience the advantages of interactive e-learning.